L'ibridismo nell'opera primoleviana - Tichoniuk -Wawrowicz, Ewa (Wydawnictwo Naukowe UAM, 2008)
The paper is dedicated to the writer's fascination of complexity of the universe and hybridism. He used to call himself a centaur, because of his double disposition: novelist/poet and chemist. Levi, stretched between being Italian and Jew, writer and chemist, commentator and translator, between the «daily» and «nightly» writing, was able to transcend the common division between letters and science. He was interested in contamination, mixture, mutation, and discussed hybridity in many essays and literary scherzos to show convolutions of human condition and prolific richness of life. Levi's unusual powers of observation combine with an abundance of themes and literary forms, which proves that his works are marked by hybridism at morphological level as well.
Hybridism in Primo Levi's writings
Keywords: Levi Primo; Hybridism